Implementasi Manajemen Penilaian Pendidikan Berbasis Digital di MAS YPP Jamanis - Acep Ridwan Maulana; Neneng Nurmalasari (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2025)
The aim of this research is to find out how digital-based educational assessment management is at MAS YPP Jamanis. The subjects in this research were the Head of MAS YPP Jamanis, Deputy Head of Curriculum, Teacher Council and Students. The type of research used in this research is qualitative. The data collection techniques used are observation, interviews and documentation techniques. Data analysis techniques in research are carried out by collecting data, reducing data, presenting data and final conclusions. Testing the validity of the data in this study used triangulation techniques. The results of this research concluded that the implementation of digital-based educational assessment management at MAS YPP Jamanis was proven to be able to increase the effectiveness of teacher performance. Educational assessment management is a collection of efforts consisting of planning, organizing, implementing and evaluating to measure student learning outcomes. The large number of devices that require rejuvenation and the limited number of reliable human resources are challenges for MAS YPP Jamanis so that this assessment scheme can continue and be developed in the future.